Factors Affecting Quality and Health Promoting Compounds during Growth and Postharvest Life of Sweet Cherry (Prunus avium L.) - Correia, Sofia; Schouten, Rob; Silva, Ana P.; Gonçalves, Berta (Frontiers in Plant Science, 2017)
Sweet cherries are attractive fruits due to their taste, colour, nutritional value and beneficial health effects. Sweet cherry is a highly perishable fruit and all quality attributes and the level of health promoting compounds are affected by growth conditions, picking, packing, transport and storage. During production, the correct combination of scion x rootstock will produce fruits with higher firmness, weight, sugars, vitamins and phenolic compounds that boost the fruit antioxidant activity. Orchard management, such as applying drip irrigation and summer pruning, will increase fruit sugar levels and total phenolic content, while application of growth regulators can result in improved storability, increased red colouring, increased fruit size, and reduced cracking. Salicylic acid, oxalic acid, acetylsalicylic acid and methyl salicylate are promising growth regulators as they also increase total phenolics, anthocyanins and induce higher activity of antioxidant enzymes. These growth regulators are now also applied as fruit coatings that improve shelf-life with higher antioxidant enzyme activities and total phenolics. Optimizing storage and transport conditions, such as hydro cooling with added CaCl2, chain temperature and relative humidity control, are crucial for slowing down decay of quality attributes and increasing the antioxidant capacity. Application of controlled atmosphere during storage is successful in delaying quality attributes, but lowers ascorbic acid levels. The combination of low temperature storage in combination with modified atmosphere packaging (MAP) is successful in reducing the incidence of fruit decay, while preserving taste attributes and stem colour with a higher antioxidant capacity. A new trend in MAP is the use of biodegradable films such as micro-perforated polylactic acid film that combine significant retention of quality attributes, high consumer acceptability and a reduced environmental footprint. Another trend is to replace MAP with fruit edible coatings. Edible coatings, such as various lipid composite coatings, have advantages in retaining quality attributes and increasing the antioxidant activity (chitosan) and are regarded as approved food additives, although studies regarding consumer acceptance are needed. The recent publication of the sweet cherry genome will likely increase the identification of more candidate genes involved in growing and maintaining health related compounds and quality attributes.